Carving Up Participation: Sense-Making and Sociomorphing for Artificial Minds - Zebrowski, Robin L.; McGraw, Eli B. (Frontiers in Neurorobotics, 2022)
AI (broadly speaking) as a discipline and practice has tended to misconstrue social cognition by failing to properly appreciate the role and structure of the interaction itself. Participatory Sense-Making (PSM) offers a new level of description in understanding the potential role of (particularly robotics-based) AGI in a social interaction process. Where it falls short in distinguishing genuine living sense-makers from potentially cognitive artificial systems, sociomorphing allows for gradations in how these potential systems are defined and incorporated into asymmetrical sociality. By side-stepping problems of anthropomorphism and muddy language around it, sociomorphing offers a framework and ontology that can help researchers make finer distinctions while studying social cognition through enactive sociality, PSM. We show here how PSM and sociomorphing, taken together and reconceived for more than just social robotics, can offer a robust framework for AGI robotics-based approaches.